2021
DOI: 10.3390/genes12081146
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase θ: A Cancer Drug Target with Reverse Transcriptase Activity

Abstract: The emergence of precision medicine from the development of Poly (ADP-ribose) polymerase (PARP) inhibitors that preferentially kill cells defective in homologous recombination has sparked wide interest in identifying and characterizing additional DNA repair enzymes that are synthetic lethal with HR factors. DNA polymerase theta (Polθ) is a validated anti-cancer drug target that is synthetic lethal with HR factors and other DNA repair proteins and confers cellular resistance to various genotoxic cancer therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 87 publications
(163 reference statements)
0
14
0
Order By: Relevance
“…A recent study on the fruit fly showed that TMEJ compensates for the BRCA2 dependent loss of HR on Holliday junction resolvases by using HR-intermediates that suppress mitotic crossing over and preserve the genomic stability [ 44 ]. BRCA2 deficiency has been shown to be synthetic lethal with disruption of either RAD52 or polymerase theta (POLQ) [ 26 , 27 , 45 , 46 , 47 , 48 ] or both [ 49 ]. Both RAD52 and POLQ are, therefore, important backup pathways for DSB repair and RS responses in BRCA2 deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the fruit fly showed that TMEJ compensates for the BRCA2 dependent loss of HR on Holliday junction resolvases by using HR-intermediates that suppress mitotic crossing over and preserve the genomic stability [ 44 ]. BRCA2 deficiency has been shown to be synthetic lethal with disruption of either RAD52 or polymerase theta (POLQ) [ 26 , 27 , 45 , 46 , 47 , 48 ] or both [ 49 ]. Both RAD52 and POLQ are, therefore, important backup pathways for DSB repair and RS responses in BRCA2 deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Microhomology-mediated end joining (MMEJ) and single-strand annealing (SSA) are mutagenic NHEJ-related pathways that have been reviewed in more detail elsewhere [3,29,30] and are beyond the scope of this review. It is relevant to note that MMEJ may be initiated by PARP1 [29] and is facilitated by polθ [31].…”
Section: Nonhomologous End-joiningmentioning
confidence: 99%
“…It is commonly overexpressed in many cancers, typically correlating with other HR defects and worse patient outcomes. Furthermore, overexpression of polθ has been shown to contribute to resistance to DNA-damaging agents such as radiotherapy, chemotherapy agents, and PARPi [31]. Following the discovery of a selective polθ inhibitor and using knockout models, it was identified that inhibition or loss of polθ can induce synthetic lethality in BRCA-and HR-deficient cells [31,127].…”
Section: Dna Polymerasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the role of DNA polymerases in DNA replication and repair, it is not surprising that any disruption or irregularity in the function of DNA polymerases can disrupt the genomic stability of an individual, thereby increasing the rate of gene mutations and an individual's vulnerability to cancer (Lange et al, 2011). Of the different DNA polymerases, DNA polymerase θ (POLQ) has become an attractive target in anti-cancer drug discovery strategies (Chen and Pomerantz, 2021). This multi-functional DNA polymerase plays a key role in tumors with deficient homologous recombination (HR).…”
Section: Introductionmentioning
confidence: 99%